A Kid's Guide to How Fruit Grows - Ayers, Patricia (New York : Rosen Pub. Group's PowerKids Press, 1999)
This book explains the basics of growing different kinds of fruit and gives simple instructions for planting and growing strawberries.
Includes index.
Includes glossary.
K-3
AR Accelerated Reader
Keywords: Fruit culture; Strawberries